The Effect of Foot Reflexology Massage on Fatigue and Sleep Quality in Hemodialysis Patients - Raheleh Rajabi PhD; Fatemeh Akhlaghi MSN; Neda Asadi PhD; Fatemeh Zamani Babgohari Bsc; Fatemeh Arabpoor Bsc (SAGE Open Nursing)
Background and Aim Hemodialysis patients experience fatigue due to factors such as toxic compounds in the bloodstream, fluid, and electrolyte disorders. Despite resting, they still feel tired and report poor sleep quality. This study aimed to investigate the effect of foot reflexology massage on reducing fatigue and improving sleep quality in hemodialysis patients. Methods This quasi-experimental study was conducted on hemodialysis patients in southeastern Iran. Eligible patients were selected through purposive sampling and allocated to either the intervention group ( n  = 25) or the control group ( n  = 25). The intervention group received foot reflexology massage three times weekly for three weeks, while the control group received routine care. Data were collected using the Pittsburgh Sleep Quality Index (PSQI) and Piper Fatigue Scale at three time points: pre-intervention, immediately post-intervention, and two weeks after intervention. Results The findings showed that the mean score of sleep quality in the intervention group decreased from 16.23 before the intervention to 3.31 two weeks after the intervention ( p  <  . 001). Furthermore, the mean fatigue score in the intervention group decreased from 8.63 before the intervention to 3.11 two weeks after the intervention ( p  <  . 001). Conclusion The results of this study showed that foot reflexology can reduce fatigue and increase sleep quality in hemodialysis patients. As a simple, feasible, and non-invasive method without complications, reflexology can be used by nurses to reduce fatigue and increase sleep quality in HD patients.